Discourses of “religion” in public health research: Constructing religious facilitators, barriers, and subjects of health as exercises of power - Tyler J. Fuller (SSM: Qualitative Research in Health)
Public health scholars increasingly reference “religion” as a social determinant of health, often framing it as a facilitator or barrier to population health or health promotion. Yet the category remains undertheorized in public health research. Drawing on interpretive approaches and critical religious studies, I interrogate how public health scholars conceptualize and operationalize “religion” in peer-reviewed literature. Using ethnographic content analysis, I analyzed 271 research articles published between 2010 and 2022 in ten high-impact generalist public health journals. Rather than offering a systematic review of what has been published about religion, this analysis asks how “religion” is constructed and made legible within public health discourse. I examine the normative assumptions and power structures embedded in scholarly representations of religion. I identify five dominant discursive patterns: (1) religious beliefs as barriers to public health; (2) religious institutions as partners in health promotion; (3) religious practices as sources of social capital; (4) religion as a barrier to LGBTQ + health; and (5) Asian religions as barriers to health. I argue that public health discourse often constructs “religion” through Protestant-inflected assumptions, privileging certain traditions and marginalizing others. These discourses reinforce binaries of “good religion” and “bad belief,” contributing to epistemic injustice and shaping health subjectivities in ways that can undermine equity. This matters for public health because marginalization and inequity are themselves barriers to health and well-being. This article calls for greater reflexivity and attention to positionality in public health research on religion and offers tools for critically engaging the discursive power of our own scholarship.